(untitled) (Indian Journal of Arid Horticulture, 2025)
Perlette is an important grape cultivar, which is extensively grown in Punjab, Haryana and adjoining areas of Rajasthan. One of the major factor for profitable grape production is the judicious application of fertilizes. However, farmers are not judiciously applying manures and fertilizers as per the recommendations. The information regarding nutrient removal pattern helps in assessing the nutrient requirement of a plant. This further helps in standardization of fertilizer requirement of plants. Very little information is available regarding nutrients removal by grape vines. Hence a field experiment was conducted on uniform eight years old perlette grape vines, to find out the nutrient removal through different parts of the plant. The grape vines were yielding 31kg/vine. The soil of the experimental field was sandy loam and calcareous alkaline in reaction (pH 8.4), EC 0.23 dS m, low in organic carbon (0.33%), medium in available P (17.60 kg/ha) and was high in available K (374 kg/ha). The vines were pruned to 3-4 buds per cane with a total number of 45 canes/ vine at the time of annual pruning during January, 2005. Cultural practices were followed as per PAU, recommendation (Anonymous 2005).